Antigua and Barbuda : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Antigua and Barbuda. (IMF Staff Country Reports; Country Report, 2007)
The staff report for the 2006 Article IV Consultation on Antigua and Barbuda highlights the economic backdrop and outlook for restoring sound public finances. The government of Antigua and Barbuda has adopted an ambitious reform program in its endeavor to pull the economy from decades of fiscal weakness and declining growth rates. The tax reform, including the imminent implementation of the value-added tax, is a major achievement. At the same time, it will be important to strengthen tax administration and tax compliance.